Four Promoters of IRF5 Respond Distinctly to Stimuli and are Affected by Autoimmune-Risk Polymorphisms - Clark, Daniel N.; Read, R. D.; Mayhew, Vera; Petersen, Stephen C.; Argueta, Lissenya B.; Stutz, Lance A.; Till, Rodney E.; Bergsten, Sean M.; Robinson, Brandon S.; Baumann, Douglas G.; Heap, J. C.; Poole, Brian D. (Frontiers in Immunology, 2013)
Introduction: Autoimmune diseases such as systemic lupus erythematosus, rheumatoid arthritis and multiple sclerosis affect millions of people worldwide. Interferon regulatory factor 5 (IRF5) contains polymorphisms associated with these autoimmune diseases. Two of these functional polymorphisms are found upstream of the IRF5 gene. rs2004640, which is a single nucleotide polymorphism (SNP) and the CGGGG insertion/deletion (indel) were studied. IRF5 uses four different promoters for its four first exons: 1A, 1B, 1C and 1D. Each promoter was analyzed, including functional differences due to the autoimmune-risk polymorphisms. Results: IRF5 promoters were analyzed using ChIP-Seq data (ENCODE database) and the FactorBook database to define transcription factor binding sites. To verify promoter activity, the promoters were cloned into luciferase plasmids. Each construct exhibited luciferase activity. Exons 1A and 1D contain putative PU.1 and NFkB binding sites. Imiquimod, a Toll-like receptor 7 ligand, was used to activate these transcription factors. IRF5 levels were doubled after imiquimod treatment (p